2014
DOI: 10.1007/s11356-014-3595-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic shellfish toxins in Dinophysis caudata picked cells and in shellfish from the East China Sea

Abstract: We reported previously that okadaic acid (OA) and dinophysistoxin-1 (DTX1) were responsible for diarrhetic shellfish poisoning (DSP) incidents due to consuming cultivated mussels (Mytilus galloprovincialis) in coastal cities near the East China Sea in May 2011. Pectenotoxin-2 (PTX2) and its seco acids were also present in these mussels. Causative species of microalgae were not identified because detailed information on the location of the contaminated shellfish was not recorded. In order to explore potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…GYM and SPX1 were detected in almost all seasons in different shellfish samples, although the highest levels of GYM occurred in winter. This result matches the data that detected from samples in May 2012 from the East China Sea [ 13 ].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…GYM and SPX1 were detected in almost all seasons in different shellfish samples, although the highest levels of GYM occurred in winter. This result matches the data that detected from samples in May 2012 from the East China Sea [ 13 ].…”
Section: Resultssupporting
confidence: 91%
“…In China, OA is recognized as the main cause of diarrheic shellfish poisoning (DSP) [ 3 , 4 , 8 , 13 ]. Among the five toxins tested in this study, OA was the only one found in all locations, with the highest prevalence (37.8%) occurring in QD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, poisoning events and victims frequently occurred due to consumption of contaminated seafood [6][7][8]. For example, diarrhetic shellfish poisoning (DSP) as a familiar poisoning event is related to OA-group toxins, including OA and its derivatives dinophysistoxin-1 (DTX1) and epimer DTX2, accumulated by crabs, mussels, etc [9][10][11][12]. Although no victims were recorded by DSP events, a link was hypothesized between exposure to OA-group toxins and tumor enhancement [13][14].…”
Section: Introductionmentioning
confidence: 99%